An animal model of panic vulnerability with chronic disinhibition of the dorsomedial/perifornical hypothalamus - Johnson, Philip L. (2012)
Panic disorder (PD) is a severe anxiety disorder characterized by susceptibility to induction of panic attacks by subthreshold interoceptive stimuli such as sodium lactate infusions or hypercapnia induction. Here we review a model of panic vulnerability in rats involving chronic inhibition of GABAergic tone in the dorsomedial/ perifornical hypothalamic (DMH/PeF) region that produces enhanced anxiety and freezing responses in fearful situations, as well as a vulnerability to displaying acute panic-like increases in cardioexcitation, respiration activity and “flight” associated behavior following subthreshold interoceptive stimuli that do not elicit panic responses in control rats. This model of panic vulnerability was developed over 15 years ago and has provided an excellent preclinical model with robust face, predictive and construct validity. The model recapitulates many of the phenotypics features of panic attacks associated with human panic disorder (face validity) including greater sensitivity to panicogenic stimuli demonstrated by sudden onset of anxiety and autonomic activation following an administration of a sub-threshold (i.e., do not usually induce panic in healthy subjects) stimulus such as sodium lactate, CO(2), or yohimbine. The construct validity is supported by several key findings; DMH/PeF neurons regulate behavioral and autonomic components of a normal adaptive panic response, as well as being implicated in eliciting panic-like responses in humans. Additionally, Patients with PD have deficits in central GABA activity and pharmacological restoration of central GABA activity prevents panic attacks, consistent with this model. The model’s predictive validity is demonstrated by not only showing panic responses to several panic-inducing agents that elicit panic in patients with PD, but also by the positive therapeutic responses to clinically used agents such as alprazolam and antidepressants that attenuate panic attacks in patients. More importantly, this model has been utilized to discover novel drugs such as group II metabotropic glutamate agonists and a new class of translocator protein enhancers of GABA, both of which subsequently showed anti-panic properties in clinical trials. All of these data suggest that this preparation provides a strong preclinical model of some forms of human panic disorders.